THE DISCERNING TRAVELER AND SUSTAINABLE TOURISM IN ASEAN – A CRITIQUE - barnett, leonard (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2017)
This academic paper examines current opportunities and challenges for tourism in the ASEAN region and discusses the need for sustainable approaches. After elaborating the ASEAN context, it investigates etiological linkages between the so-called ‘discerning’ traveler and sustainable approaches to tourism and provides a robust critique of these. In examining current trends in tourism theory and practice and while acknowledging serious criticisms of theoretical development in the area, the study explores the conceptual linkages between postmodernism, sustainability and development. Having explained the positive and negative impacts of tourism, this paper introduces the notion of the postmodern ‘discerning traveler’ and positions this within sustainable tourism and current theoretical developments. It introduces a typology of discerning travelers and highlights the implications of each for tourism generally and in the ASEAN Economic Community (AEC), Greater Mekong Subregion (GMS), tourism authorities and companies. Finally, the study provides a critique of the notion of the ‘discerning’ traveler and examples of future research projects which examine how to embody sustainability and attract the high-end, low-impact discerning visitor.